Improvement in Optoelectronic Properties of Bismuth Sulphide Thin Films by Chromium Incorporation at the Orthorhombic Crystal Lattice for Photovoltaic Applications - Tanzeela Fazal; Shahid Iqbal; Mazloom Shah; Bushra Ismail; Nusrat Shaheen; Hamad Alrbyawi; Murefah Mana Al-Anazy; Eslam B. Elkaeed; H. H. Somaily; Rami Adel Pashameah; Eman Alzahrani; Abd-ElAziem Farouk (Molecules, 2022)
By using the chemical bath deposition approach, binary bismuth sulphides (Bi2S3) and chromium-doped ternary bismuth sulphides (Bi2−xCrxS3) thin films were effectively produced, and their potential for photovoltaic applications was examined. Structural elucidation revealed that Bi2S3 deposited by this simple and cost-effective method retained its orthorhombic crystal lattice by doping up to 3 at.%. The morphological analysis confirmed the crack-free deposition, hence making them suitable for solar cell applications. Optical analysis showed that deposited thin films have a bandgap in the range of 1.30 to 1.17 eV, values of refractive index (n) from 2.9 to 1.3, and an extinction coefficient (k) from 1.03 to 0.3. From the Hall measurements, it followed that the dominant carriers in all doped and undoped samples are electrons, and the carrier density in doped samples is almost two orders of magnitude larger than in Bi2S3. Hence, this suggests that doping is an effective tool to improve the optoelectronic behavior of Bi2S3 thin films by engineering the compositional, structural, and morphological properties.